(untitled) (Universal International Scientific Journal, 2026)
This article discusses the pedagogical importance of interactive games in the development of logical thinking in children. It also examines the issues of developing independent thinking, problem-solving, and decision-making skills in children through gaming activities. The role of interactive games in the educational process, methods of their use, and their impact on children’s intellectual development are analyzed from a scientific and pedagogical point of view.